A study of the Pycnonotus bulbul species complex in Southern Africa - Lloyd, Penn (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1995)
The three Pycnonotus bulbuls endemic to Africa, P. barbatus, P. nigricans and P. capensis, occupy mutually exclusive distributions in southern Africa. These species are closely related and appear to occupy very similar ecological niches, only in different regions. Using a multifaceted approach, this study attempts to explain the ecology of this species complex. All three species show similar physiological responses to temperature extremes, and are therefore unlikely to be directly limited by environmental temperature. However, their distributions are highly correlated to a complex of environmental variables, particularly winter minimum temperatures, the coefficient of variation in mean annual rainfall, and the seasonality of rainfall. This combination of environmental parameters can be used to predict the distributions of at least one of the species, P. nigricans, accurately. An analysis of the vocalizations and behaviour of the three species revealed that, whilst P. capensis has a number of recognizably different vocalizations, those of P. barbatus and P. nigricans are very similar. The three have nearly identical behaviours, particularly courtship and pre-copulatory behaviours. The mate recognition systems of the three are therefore extremely similar. P. barbatus is territorial during the breeding season, and exhibits highly structured-variation in male territorial song at the level of the local neighbourhood. The literature pertaining to song dialects is reviewed, and a new hypothesis is postulated to explain song-matching in terms of neighbour/stranger discrimination and the possible existence of cooperative territory defence. A survey of the eastern Cape region, where all three species come into contact, showed that extensive hybridization is taking place between each species pair. Phenotypically, this hybridization is restricted to narrow hybrid zones, that are considered to be stable in both time and place. The evolutionary and ecological significance of these zones to the distributions of the species is discussed, and it is proposed that the zones are maintained by selection acting on differentially-adapted genomes along an environmental gradient.
Keywords: Bulbuls -- Ecology -- South Africa -- Eastern Cape; Songbirds -- Ecology -- South Africa -- Eastern Cape; Birds -- Ecology -- South Africa -- Eastern Cape